Selective solar absorbing coating for flat-plate solar collector - ZHANG TONGWEI; WU JIANGHONG; WANG YONG (2016)
The invention provides a selective solar absorbing coating for a flat-plate solar collector. The selective solar absorbing coating comprises a base layer, an alloy plastic layer, a non-metal composite layer and a metal oxidation layer; an alloy plastic layer is arranged on the surface of the base layer, a copolymerization chemical compound is adopted in the alloy plastic layer, and a selective absorbing layer is formed by the non-metal composite layer and the metal oxidation layer; and the selective solar absorbing coating has the excellent solar selective absorbing characteristic, is firm, has the higher bonding strength and good weather fastness and meanwhile has the higher production efficiency during production. 本发明提供种用于平板太阳能集热器的选择太阳能吸收涂层，包括基层、合金塑料层、非金属复合层和金属氧化层，所述基层表面设置有合金塑料层，所述合金塑料层采用共聚化合物，所述非金属复合层与金属氧化层形成选择吸收层。本发明具有优良的太阳能选择性吸收特性，且膜层牢固，具有较高的结合强度和良好的耐候性，同时在生产时具有较高的生产效率。